Kaji teoritis EMS (Engine Management System) dengan variasi temperatur air pendingin dan beban kerja pada kondisi stasioner pada kendaraan Toyota Avanza - Angga Wahyu Pramayudha; Gunarko Gunarko; Ardyanto Darmanto; F A Widiharsa (TURBO [Tulisan Riset Berbasis Online], 2020)
EMS is a control system on the engine to regulate the proper mixing of air and fuel, accurate ignition timing, and control of other systems on the engine, according to the conditions and workload of the vehicle. The EMS component consists of sensors, ECU, and actuator. Engine control is fully regulated by the ECU. After getting data from the sensor, the ECU sensor will signal the actuator to control the engine, so that the work of the engine can be controlled according to the conditions of the engine. The effect of the cooling water temperature sensor is very large at stationary (Idle Speed Control/ISC). This research method is carried out by varying the temperature of cooling water (Engine Coolant Temperature/ECT) to get the mass of gasoline, air mass, air fuel ratio, engine speed, ignition angle, and gasoline consumption at each ISC load. The results of the research and data processing show that gasoline consumption will decrease every time the cooling water temperature increases. The AC (Air Conditioner) load ranges from 1,123 x 10-2 to 2,164 x 10-2 kg/hour, the power steering load ranges from 6,311 x 10-3 to 9,482 x 10-3 kg/hour, the electrical load ranges from 6,608 x 10-3 to 7,876 x 10-3 kg/hour and without load ranges from 6,024 x 10-3 to 7,920 x 10-3kg/hour. From these data it can be concluded that the effect of the ECT sensor is very large on engine performance at stationary rotation (ISC).Keywords: Sensor, ECU, Actuator.